2000
DOI: 10.1016/s0304-3959(00)00290-6
|View full text |Cite
|
Sign up to set email alerts
|

Supraspinal cholecystokinin may drive tonic descending facilitation mechanisms to maintain neuropathic pain in the rat

Abstract: Complete or partial spinal section at T(8) has been shown to block tactile allodynia but not thermal hyperalgesia following L(5)/L(6) spinal nerve ligation (SNL), suggesting the supraspinal integration of allodynia in neuropathic pain. In the present study, the possibility of mediation of nerve injury-associated pain through tonic activity of descending nociceptive facilitation arising from the rostroventromedial medulla (RVM) was investigated. Specifically, the actions of brainstem cholecystokinin and the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
113
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(123 citation statements)
references
References 36 publications
9
113
0
1
Order By: Relevance
“…These studies have confirmed and extended our previous observations showing that pharmacological administration of CCK into the RVM, or into sites somewhat dorsal to the RVM (Kovelowski et al, 2000), induces thermal and mechanical hypersensitivity in naive rats. These effects were time dependent, were mediated via the CCK 2 receptors, and were abolished by lesions of the DLF, suggesting activation of a descending pain facilitation mechanism.…”
Section: Discussionsupporting
confidence: 89%
“…These studies have confirmed and extended our previous observations showing that pharmacological administration of CCK into the RVM, or into sites somewhat dorsal to the RVM (Kovelowski et al, 2000), induces thermal and mechanical hypersensitivity in naive rats. These effects were time dependent, were mediated via the CCK 2 receptors, and were abolished by lesions of the DLF, suggesting activation of a descending pain facilitation mechanism.…”
Section: Discussionsupporting
confidence: 89%
“…Spinal nociception is reported to be enhanced via descending facilitation which can contribute to the development and maintenance of chronic pain (Burgess et al, 2002;Kovelowski et al, 2000;Porreca et al, 2002). During acute nociception, both descending facilitatory and inhibitory pathways are activated and are counterbalanced.…”
Section: Descending Pain Pathway (Control Inhibition and Facilitation)mentioning
confidence: 99%
“…One hypothesis suggests that central sensitization at the level of the spinal dorsal horn is maintained independently of primary afferent input (Sandkuhler and Liu, 1998) since input from the periphery is reportedly insufficient to maintain spinal modifications in sensory processing and ultimately neuropathic pain (Burgess et al, 2002;Sun et al, 2005;Xie et al, 2005). Another view suggests that mechanisms at the spinal dorsal horn level require continuous facilitatory input from supraspinal structures Carlson et al, 2007;Gardell et al, 2003;Kauppila et al,1998;Kovelowski et al, 2000;Ossipov et al, 2000;Pertovaara et al, 1997Pertovaara et al, , 2001Porreca et al, 2001;Saade et al, 2006aSaade et al, ,b, 2007Suzuki et al, 2002Suzuki et al, , 2004aVeraPortocarrero et al, 2006). However, in both animal models and humans effects of peripheral neuropathy including peripheral neurodegeneration, altered Na + and K + ion channel expression (Coward et al, 2001a,b;Hong et al, 2004;Hong and Wiley, 2006;Joshi et al, 2006;Matthews et al, 2006;Shembalkar et al, 2001), and abnormal impulse discharge (Nordin et al, 1984;Nystrom and Hagbarth, 1981) in sensory afferents have been shown to persist several weeks/months (Casula et al, 2004;Coward et al, 2000;Fried et al, 1991;Kretschmer et al, 2002;Pan et al, 2001;Pertin et al, 2005;Roytta et al, 1999;Seltzer et al, 1991b).…”
Section: Introductionmentioning
confidence: 99%